Understanding co-operative R&D activity: Evidence from four European countries - Laura Abramovsky; Elisabeth Kremp; Alberto López; Helen Simpson (Institute for Fiscal Studies (IFS), 2005)
This paper investigates co-operative research activity by firms using data from the 3rd Community Innovation Survey for four countries, France, Germany, Spain and the UK. We build on the Cassiman and Veugelers (CV) (2002) study of Belgian manufacturing firms, by incorporating information on the service sector, and considering the role of public support in affecting firms' decisions to co-operate. Our results support those in CV, in that we find a positive relationship between the likelihood of undertaking co-operative R&D and both incoming knowledge spillovers and the extent to which firms find strategic methods important in appropriating the returns to innovative activity. We find that public support is positively related to the probability of undertaking co-operative agreements particularly with regard to the likelihood of co-operation with the research base. We find some evidence, in particular for Spain, that firms carry out co-operative R&D to overcome excessive perceived risks and financial constraints.
Keywords: O31; O32; L24; 330; R&D co-operation; spillovers; joint ventures; CIS; Forschungskooperation; Industrielle Forschung; Spillover-Effekt; Joint Venture; EU-Staaten